Yield Response of Soybean (Glycine max L.) Genotypes to Water Deficit Stress - Mimi, Afsana; Mannan, MA; Khaliq, QA; Mia, MA Baset (Bangladesh Agronomy Journal, 2017)
An experiment was carried out at research field of Agronomy, Department of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur from December 2013 to April 2014. Four soybean genotypes viz. i) G 00022 ii) Galarsum iii) BARI Soybean-5 and iv) G 00197 were grown in the field to evaluate the effects of water deficit stress on dry matter accumulation and yield. Plants were subjected to water stress that is irrigation was withdrawn at Blooming stage (R1) and Full Pod (R4 stages up to maturity. Dry matter accumulation, yield and yield components were reduced by the soil water deficit stress and reduction was higher at R1 stage than R4 stage of water stress. Among the genotypes, G 00022 showed the highest tolerance, while G 00197 was highly susceptible in all the water stress conditions. It was found that higher water deficit stress tolerance in G 00022 was associated with higher accumulation of leaf, stem, root and total dry matter under water stress condition. Bangladesh Agron. J. 2016 19(2): 51-60